Political marketing: factors influencing trust in Putin’s presidential campaign 2018 - Morgunova, Svetlana (2019)
The way elections are carried out today has been changed dramatically. Electorate has become a target market for political parties and politicians. To attract target market (electorate) more marketing tools and techniques are being used. Thus, any political campaign is carried out today using the tools and techniques of political marketing. In today‟s changing globalised world it is quite important to understand how to obtain political market (voters) and establish trust to make this political market more sustainable.